Modul pemakanan ibu-ibu: ke arah pengurangan reaksi alergi dalam kalangan bayi yang menyusu secara eksklusif - Abdul Ghani, Radiah; Mahasan, Ainun Syuhada; Mohd Shukri, Nor Azwani; Ibrahim, Muhammad (2021)
The maternal dietary guideline module is developed to provide a guideline for pregnant and breastfeeding mothers in to reduce the risk of allergic reaction among babies. The module is in the form of pocketbook that can be used by the Breastfeeding Peer Counselors (BPC) to educate the mothers in order to prevent the allergic reaction.